Cardiocirculatory intraoperative assessment during single-shot caudal anaesthesia in children: comparison between levobupivacaine and ropivacaine - A. Gentili; L. Pasini; V. Bachiocco; V. Landuzzi; L. Giuntoli; M. Lima; S. Baroncini (PAGEPress Publications, 2012)
Background: Caudal block with levobupivacaine or ropivacaine is the most commonly used regional anaesthesia in children. Methods: The aim of study was to compare the cardiocirculatory profile induced in two matched groups of young patients, submitted to caudal anaesthesia with levobupivacaine or ropivacaine for an elective subumbilical surgery. Sixty children were enrolled: thirty received levopubivacaine 0.25% and thirty ropivacaine 0.2%. Intraoperative heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP) were monitored at following times: Ta0 (after anaesthesia induction), Ta1 (after caudal anaesthesia), Ta2 (five minutes later), Ta3 (ten minutes later), Ts1 (at surgical incision), Ts2, Ts3, Ts4, Ts5 (every 10 minutes during surgery), Taw (at the awakening). Results: In both groups the cardiocirculatory trend remained within normal ranges at all times considered, demonstrating the safety of the method with both drugs. Both groups showed a similar trend at the different monitoring times: low decrease in HR, SBP and DBP after caudal block, slight increase in parameters after skin incision, slight decrease during surgery, increase at awakening. Regarding SBP and DBP, the levobupivacaine group children generally showed higher levels compared to the ropivacaine group, especially for DBP. Conclusions: Paediatric caudal anaesthesia is an effective method with an very infrequent complication rate. Possible hypotheses for differing haemodynamic behaviour could include a stronger vasoconstriction reflex of innervated areas during caudal anaesthesia with levobupivacaine and a lower levobupivacaine induced block of the sympathetic fibers, related to different pharmacokinetic profile of low concentrations of the local anaesthetics used in paediatric epidural space.